PENGEMBANGAN MEDIA FLIPBOOK BERBASIS KEARIFAN LOKAL KABUPATEN JEPARA TEMA 8 SUBTEMA 3 KELAS IV DI SEKOLAH DASAR - Tania Ike Nur Rahmawati; Khusnul Fajriyah; A. Y. Soegeng Ysh (STKIP Subang, 2022)
This study aims to produce flipbook media based on local wisdom of Jepara Regency Theme 8 Sub-theme 3 grade IV in elementary schools that meet valid and practical criteria. This type of research is research and development (R&D). The development model used is ADDIE, namely analyze, design, development, implementation, and evaluation. The research instrument includes a validation questionnaire sheet and a practicality questionnaire sheet (responses of teachers and students). The results showed that the flipbook media based on local wisdom of Jepara Regency Theme 8 Sub-theme 3 class IV in Elementary School obtained a validation percentage by media experts of 97.5% with very valid criteria, the percentage of validation by material experts was 93.3% with very valid criteria. . The average percentage of validation is 95.4% with very valid criteria. The percentage of practicality tests by teachers obtained 99.1% with very practical criteria. The results of the student questionnaire obtained 94.5% with very practical criteria. So that the results of the practicality test meet the very practical criteria with an average percentage of 96.8%. Based on the results of the study, it can be concluded that this study produced a flipbook media based on local wisdom in Jepara Regency, theme 8 sub-theme 3, grade IV in elementary schools that was valid and practical.